EFFECTIVENESS GYMNASTICS ELDERLY AGAINST RESPIRATORY IN THE HEALTH CENTERS AREA OF SIMPANG KAWAT JAMBI 2018 - Kaimuddin Anwar; Cek Masnah (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2018)
ABSTRACT The increasing age of life expectancy means that it is the number of the elderly in Indonesia, this is a logical consequence of successful development in Indonesia. to be a burden on society. Elderly exercisers is designed specifically to train body parts as well as the waist, feet and hands in order to get the stretch for the elderly, but not excessive movement. This research aims to identify precision elderly gymnastics in increasing the strength of the respiratory and pulmonary ventilation function in the elderly. The function is used as a foundation for the elderly in the community. Research methods, quantitative research using the method of quasi-circling or causal comparative. Health centers of the Jambi Simpang Kawat city. The research design used was the control group pretest-posttest design. The intervention group and the control group were measured both before and after the intervention at the time of research. After the intervention is expected to happen, change or influence on other variables. The results of this research have identified the characteristics of elderly (age, height, weight, gender) that follow gymnastics, elderly health centers in the city of Jambi, Wire Junction gymnastics, elderly effects on respiratory muscle strength (p value = 0.006) and lung function (p value = 0.018) on the elderly who routinely carry out gymnastics elderly health in the health center area of Simpang Kawat Jambi city. Advice for nursing services to the community, so that the health center routinely carries out activities of the elderly because the gymnastics affect the fitness of the elderly and reduce days of health care for the elderly.